2012
DOI: 10.1007/s10719-012-9443-9
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for the profiling, characterisation and detailed structural analysis of N-linked oligosaccharides

Abstract: Many post-translational modifications, including glycosylation, are pivotal for the structural integrity, location and functional activity of glycoproteins. Sub-populations of proteins that are relocated or functionally changed by such modifications can change resting proteins into active ones, mediating specific effector functions, as in the case of monoclonal antibodies. To ensure safe and efficacious drugs it is essential to employ appropriate robust, quantitative analytical strategies that can (i) perform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 61 publications
0
35
0
1
Order By: Relevance
“…HILIC-FD in HPLC format is not a "high resolution method", but considerable improvements in both separation time and peak resolution have been reported when switching to the finer particle sizes of UPLC [63,89]. In UPLC format, HILIC-FD is equal or perhaps slightly superior to HPAEC-PAD in separation efficiency of some structures, but requires the additional steps of labelling and cleanup with the attendant potential for introductions of bias.…”
Section: Choice Of Column Chemistries Eluent Conditions and 2-aa Or mentioning
confidence: 99%
See 3 more Smart Citations
“…HILIC-FD in HPLC format is not a "high resolution method", but considerable improvements in both separation time and peak resolution have been reported when switching to the finer particle sizes of UPLC [63,89]. In UPLC format, HILIC-FD is equal or perhaps slightly superior to HPAEC-PAD in separation efficiency of some structures, but requires the additional steps of labelling and cleanup with the attendant potential for introductions of bias.…”
Section: Choice Of Column Chemistries Eluent Conditions and 2-aa Or mentioning
confidence: 99%
“…However, there is a larger body of published research employing and supporting the 2-AB label, including a web-based glycan identification database centred upon relative retention times [96][97][98]. HILIC users are about evenly split, with strongly entrenched preferences for separation of 2-AA-labelled glycans on polymeric amine-based columns [64,94,[99][100][101], or for separation 2-AB-labelled glycans on silica-based (or silica-polymer hybrid) amide-based columns [15,63,86].…”
Section: Choice Of Column Chemistries Eluent Conditions and 2-aa Or mentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been reported that cellular localization and protein structure influence/determine protein-and site-specific N-glycosylation (23,24). It should be noted that intact glycopeptide studies usually only allow the determination of glycan compositions; the identity of the oligosaccharide units and their linkage may be obtained from released glycan studies (5,6).…”
mentioning
confidence: 99%